Nutritional and morpho-anatomical characterization of Phyllostachys aurea (Poaceae, Bambusoideae, Bambuseae) foliage for Argentine livestock systems - Wawrzkiewicz, Marisa; Fernández Pepi, María Gabriela; Buzzo, Matías Osvaldo; Zucol, Alejandro Fabián; Vega, Andrea Susana (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
Bamboo cultivation in Argentina could represent a major economic activity if its various applications were revealed. This study characterized the anatomy and micromorphology of leaf blades by optical and scanning electron microscopes. Foliage leaves presented predominant parenchyma and scarce sclerenchyma. Foliage chemical and biological composition were analyzed in 3 populations of P. aurea sampled in two contrasting seasons of the year. The six samples evaluated showed 13% protein, adequate for ruminant feed. Neutral detergent fiber (aNDFom) was approximately 60% DM, a probable limiting factor for consumption. Significant differences in ADFom (acid detergent fiber) and ADLom (acid detergent lignin) favored spring results, with lower values than winter results. The presence of silica in different cell types could limit digestion. Fermentation kinetics indicated that dry matter digestibility is close to 50%, and higher in spring given lower amounts of indigestible components. In addition, all samples analyzed had a low content of immediately soluble material and a high content of potentially fermentable insoluble material. Anatomy and chemical-nutritional characterization allow P. aurea foliage to be considered in ruminant feeding. Highlights: Nutritional and morpho-anatomical studies are complementary in the evaluation of forages for ruminants. Anatomy and chemical-nutritional characterization allow aurea foliage to be considered in ruminant feeding. Silica in epidermis, trichomes, cell walls or lumen of grasses acts as structural inhibitor of microbial digestion leading to lower acceptability and DMD. The high silica content accounts for 82% of the total ash, suggesting the presence of indigestible substances. Phyllostachys aurea foliage leaves showed 13% protein, adequate for ruminant feed and neutral detergent fiber was approximately 60%DM.